2015
DOI: 10.1007/s00011-015-0880-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of a lectin from the green seaweed Caulerpa cupressoides var. lycopodium on inflammatory mediators in classical models of inflammation

Abstract: The anti-inflammatory action of CcL involves the inhibition of IL-1β, TNF-α, IL-6 and COX-2 expression and histamine H1 receptors. When locally administered, CcL exerts pro-inflammatory actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…For the treatment with C. cupressoides lectin no alteration of HO-1 expression was detected in TMJ, in spite of the results of a previous study showing that this lectin inhibited the immunoreactivity of HO-1, cytokines (IL-1β, IL-6 and TNF-α) and cyclooxygenase-2 in rat paws injected with carrageenan. 35 A HO-1 expression-dependent mechanism was also observed based on the treatment with T. toxicaria extract after the injection of zymosan in TMJ. 15 …”
Section: Discussionmentioning
confidence: 88%
“…For the treatment with C. cupressoides lectin no alteration of HO-1 expression was detected in TMJ, in spite of the results of a previous study showing that this lectin inhibited the immunoreactivity of HO-1, cytokines (IL-1β, IL-6 and TNF-α) and cyclooxygenase-2 in rat paws injected with carrageenan. 35 A HO-1 expression-dependent mechanism was also observed based on the treatment with T. toxicaria extract after the injection of zymosan in TMJ. 15 …”
Section: Discussionmentioning
confidence: 88%
“…For example, lectins from the green seaweed Caulerpa cupressoides var. lycopodium have anti-inflammatory activities, inhibiting cytokine production in carrageenan-induced rat-paw oedema models 31 . In contrast, lectins from the edible mushroom Agrocybe aegerita induce pro-inflammatory cytokine production by macrophages and promote the severity of caecal ligation and puncture-induced sepsis in mice 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory mechanism of a lectin from the green seaweed Caulerpa cupressoides var. lycopodium was investigated and showed that it decreased the carrageenan-induced rat paw edema and neutrophilic infiltration at 0.1, 1 or 10 mg/kg, and inhibited the expression of IL-1β, IL-6, TNFα and COX-2 at 1 mg/kg [ 68 ].…”
Section: Anti-inflammatory Bioactive Substances Derived From Marine Organismsmentioning
confidence: 99%